Torefaksi Tandan Kosong Sawit : Pengaruh Kondisi Proses Terhadap Nilai Kalor Produk Torefaksi - Al Qohyum Fernando; Zuchra Helwani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Empty fruit bunches can be used as alternative energy source by torrefaction process. Torrefaction is a treatment process of biomass into solid fuel within temperature range of 200-300oC in an inert condition. The aim of this research was to determine the condition of the process to the increase in calorific value torrefaction product. Torrefaction of empty fruit bunch was using fixed bed horizontal reactor with temperature (225-275oC), time (15-45 minutes) and particle size (2-6 cm). Results of the research is the calorific value and the proximate analysis torrefaction products such as moisture content, ash content, volatile content, and the content of fixed carbon. Torrefaction product calorific value in the range 17091,03-20697,13 kJ/kg.Keywords: biomass, empty fruit bunches, solid fuel, torrefaction.